2022
DOI: 10.30604/jika.v7i3.1163
|View full text |Cite
|
Sign up to set email alerts
|

Self-Help Group on Quality of Life of Patients Treating Chemotherapy

Abstract: The self-help group is one of the group therapies which provides social and psychological support for its members since they can share their problems, and information about nursing, prevention, and medication. The study was to identify the influence of self-help groups on the life quality of patients under chemotherapy treatment. The study was a quasi-experimental method with a pretest-posttest without a control group design. The samples were 35 patients under chemotherapy treatment using the purposive samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This study proves that SHG has an effect on the older adults with chronic non-communicable diseases. A study showed that there was a significant influence on the quality of life of those who were under chemotherapy treatment after self-help group intervention (Turnip, Ritarwan, SItepu, 2022). Other study showed that SHG influenced the quality of life of the elderly in Tresna Werda Social Institutions (Anggarawati & Sari, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This study proves that SHG has an effect on the older adults with chronic non-communicable diseases. A study showed that there was a significant influence on the quality of life of those who were under chemotherapy treatment after self-help group intervention (Turnip, Ritarwan, SItepu, 2022). Other study showed that SHG influenced the quality of life of the elderly in Tresna Werda Social Institutions (Anggarawati & Sari, 2021).…”
Section: Resultsmentioning
confidence: 99%